2020
DOI: 10.22335/rlct.v13i1.1292
|View full text |Cite
|
Sign up to set email alerts
|

The current outlook of human papillomavirus and its association with digestive tract cancer

Abstract: Digestive tract cancers are frequent worldwide, despite efforts to control known predisposing factors, they keep increasing, this fact suggests that human papillomavirus (HPV) may play an important oncogenic role in these pathologies. In order to argue the incidence that HPV has in the genesis of gastrointestinal tract tumors and to determine if it is a possible causal agent, the scientific literature published to date on the subject was reviewed, and was found that 4.5% of all diagnosed cancers correspond to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
2
0
1
Order By: Relevance
“…With increasingly predisposing factors, it was found that HPV might play an oncogenic role in these pathologies . Different types of HPV have large different association with epithelial tumor, and genotype distribution is related with the degree of differentiation of EC . In studies published, HPV6, 11, 16, 18, 24, 25, 26 31, 32, 33, 35, 39,42, 43, 45, 51, 52, 56, 58, 59, 66, 70, and 82 had been detected in EC tissue samples. , These studies were very consistent in suggesting the link between esophageal cancer and HPV infection, and literature information was summarized in Table .…”
Section: Discussionmentioning
confidence: 85%
“…With increasingly predisposing factors, it was found that HPV might play an oncogenic role in these pathologies . Different types of HPV have large different association with epithelial tumor, and genotype distribution is related with the degree of differentiation of EC . In studies published, HPV6, 11, 16, 18, 24, 25, 26 31, 32, 33, 35, 39,42, 43, 45, 51, 52, 56, 58, 59, 66, 70, and 82 had been detected in EC tissue samples. , These studies were very consistent in suggesting the link between esophageal cancer and HPV infection, and literature information was summarized in Table .…”
Section: Discussionmentioning
confidence: 85%
“…[ 5 ] Moreover, it is associated with colon, cervix, rectum, anus, vulva and oropharynx cancers. [ 6 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…La infección por el Virus del Papiloma Humano (VPH) ha sido reconocido como el factor etiológico más importante para el desarrollo del cáncer de cuello uterino y en la actualidad se han descrito más de 120 genotipos, siendo la tercera parte de ellos capaces de infectar el epitelio del tracto genital femenino y otros epitelios como los del canal anal, vagina, vulva, pene y cavidad oral, de tal manera que se ha estimado que el VPH es responsable del 5,2% de todos los cánceres en el mundo (5). Además de estas neoplasias, diferentes estudios lo han encontrado asociado a otros tumores (6) como los del tracto gastrointestinal (7), glándula mamaria(8) y pulmón, entre otros, situación que ha llevado a postular una posible transmisión sanguínea (9). La carcinogénesis por este virus ha sido bien establecida en las displasias y carcinomas de cuello uterino, en especial para los de alto riesgo (10), sin embargo, se ha descrito que hasta un 5% de estos tumores no se encuentran asociados con la infección persistente del VPH (11).…”
Section: Introductionunclassified